Representation of Interpersonal Conflict in Deaf Families with Child of Deaf Adult in the Film â€œCODAâ€ - HT, Nafisa Kahla; Alamiyah, Syifa Syarifah (Jurnal Dakwah dan Komunikasi, 2024)
The film â€œCODAâ€ portrays complex interpersonal conflicts within a family. These conflicts arise when a CODA and other family members have differing views on life and their aspirations, causing the CODA to balance between her dreams and responsibilities to her deaf family members. This research aims to find out the representation of interpersonal conflict in a deaf family with a Child of Deaf Adult in the movie CODA. This research uses qualitative method with Roland Barthes semiotic approach to explore the meaning of denotation, connotation, and myth, particularly within the context of interpersonal conflicts faced by family members in the film â€œCODAâ€. The results show that interpersonal conflicts are depicted through quarrels, passive-aggressive behavior, and value clashes, which arise as a result of differences in cultural identity, family expectations and hopes, adjustment and dependence, and inequality of roles and responsibilities. The movie also breaks some myths, namely the assumption that the responsibility and role of an interpreter lies only with a CODA, the myth that one's success and happiness lies in financial success and business stability, and the myth that deaf people cannot be independent and always depend on others.